…e fon sazos/Que per un gan/Er’hom bautz e ioios ! - Isabel de Riquer (Revue des Langues Romanes)
The subject of a gift is well-known to the specialists in troubadour poetry. The Lady delivers the troubadour some of her private belongings: a ring, a brooch, a glove or a cordo, as areward for his faithful service and the adulations expressed in his songs. Giraut de Bornelh who lost his lady's benevolence as a consequence of losing her glove, described it in five of his cançós. The author of two razós (the one corresponding to Si-us quier conseil, bell'amiga Alamanda, BdT 242. 69, and the one of Ges aissi del tot no·m lais, BdT 242. 36, both present only in the chansonnier Sq), created a little love story using the vague allusions found in the mentioned bornelian poems. Among the scholars, this story caused a more than hundred years-long debate regarding the so-called «glove cycle». The author of razós is defending the troubadour, severely criticizing the behaviour of the Lady. Moreover, he is using the language characteristic of a mala cansó, as if attempting to create a mala cansó in prose.